Nano-lipid Contrast Agent Combined with Ultrasound-Guided SGB in Nursing Treatment of Lymphedema after Breast Cancer Surgery: Nano-lipid Contrast Agent Combined with Ultrasound-Guided SGB - Zhang, Yuanyuan; Yuan, Jin; Zhang, Qing; Yan, Jin; Ju, Song; Yang, Ying (Cellular and Molecular Biology, 2022)
At present, the application of nano-material technology in nursing treatment is more and more extensive, so the characteristics of a variety of chips tend to the medical field. Lymphedema after breast cancer surgery is common in the recovery period of patients, so the nursing work in this period is very important. In order to explore the effect of nano-lipid contrast agent combined with ultrasound-guided SGB in the nursing treatment of breast cancer postoperative lymphedema, the application scope of nano-lipid contrast agent combined with ultrasound-guided SGB and the promotion of nano-materials on cell growth were studied. 11 cases of breast cancer patients in our hospital in 2020 were selected to study the status of lymphedema in the infection stage and recovery stage. The branching effects of nano-lipid contrast agent and ultrasound-guided SGB were evaluated. The results showed that at the same density, the recovery time of lymph tissue in the nano-lipid contrast agent combined with the ultrasound-guided SGB group was significantly shorter than that in the control group. Due to the self-healing state, the recovery time was the most significant 3-7 days after surgery. At this time, the survival rate of self-healing cells was 34.75%, and that of the nano-lipid contrast agent group was 82.37%, which indicated that the nano-lipid contrast agent combined with ultrasound-guided SGB could effectively play the role of photodynamic therapy and synergistic therapy, and inhibit the growth of tumor cells. At present, many kinds of phototherapeutic agents can inhibit the growth of cancer cells and induce apoptosis of cancer cells. Safe and efficient nano photosensitizers have broad application prospects in the field of cancer treatment.